DeLisa's Physical medicine & rehabilitation : principles and practice - Frontera, Walter R., 1955-; DeLisa, Joel A. (Lippincott Williams & Wilkins Health, 2010)
"DeLisa's Physical Medicine and Rehabilitation is the "gold standard" in the field of physical medicine and rehabilitation. It is the most modern and comprehensive book in the field. It can serve as both an introductory book for residents and a comprehensive reference book for practitioners. One volume covers physical medicine, the other rehabilitation medicine. Physical medicine covers principles of diagnosis and management, therapeutic approaches, and the management of specific conditions. Rehabilitation medicine covers the evaluation of the rehab patient, managing the rehab patient, and rehabilitation strategies and interventions"--Provided by publisher.